2013
DOI: 10.1021/mp4000234
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation Down-Regulates Expression of Organic Cation Transporters, Which Translocate β-Blockers and Fluoroquinolones

Abstract: Kidney transplanted patients are often treated with immunosuppressive, antihypertensive, and antibiotic drugs such as cyclosporine A (CsA), β-blockers, and fluoroquinolones, respectively. Organic cation transporters (OCT) expressed in the basolateral membrane of proximal tubules represent an important drug excretion route. In this work, the renal expression of OCT after syngeneic and allogeneic kidney transplantation in rats with or without CsA immunosuppression was studied. Moreover, the interactions of CsA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…In contrast to a previous study that indicated no transport of atenolol by hOCT1 (Ciarimboli et al, 2013), our data clearly demonstrated that atenolol is an excellent substrate of hOCT1 ( Figs. 2 and 3; Tables 1 and 2).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to a previous study that indicated no transport of atenolol by hOCT1 (Ciarimboli et al, 2013), our data clearly demonstrated that atenolol is an excellent substrate of hOCT1 ( Figs. 2 and 3; Tables 1 and 2).…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, Ciarimboli et al showed that hOCTs interact with several b-blockers and may also accept some b-blockers as substrates (Ciarimboli et al, 2013). Based on the physiochemical property of atenolol and the known renal elimination mechanism of organ cations, we hypothesized that renal secretion of atenolol is mediated by the hOCT2/hMATEs pathway.…”
Section: Introductionmentioning
confidence: 93%
“…However, another study by Mimura et al suggested that organic cation transporter 1 (OCT1) rather than OATP probably contributes to the interaction between atenolol and flavonoids in fruit juices [ 47 ]. It was also reported that hOCT2 at the basolateral membrane of kidney tubules lead to renal active secretion of atenolol [ 48 ]. Furthermore, the study performed by Yin et al suggested that atenolol is also a substrate of multidrug and toxin extrusion proteins (hMATE-1 and hMATE2-K) located at the apical membrane of renal tubule, thus contributing to the elimination of atenolol from blood to urine together with OCT2 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, OCT1 plays a key role in the first-pass effect through the liver and hence in the bioavailability of other cationic drugs, such as amantadine, levodopa and pramipexole [40], cimetidine [91], ciprofloxacin and other fluoroquinolones [92, 93], furamidine and pentamidine [100], lamotrigine [89], sulpiride [90], and zalcitabine [101]. …”
Section: Role Of Oct1 In Drug Transportmentioning
confidence: 99%
“…In the case of treatments based on cationic antineoplastic drugs, the combined treatment may reduce the uptake of these drugs by the tumor and hence decrease the efficacy of the chemotherapy [43]. Additional examples for such a clinically relevant interaction include antibiotics and antihypertensives [92]. …”
Section: Role Of Oct1 In Drug Transportmentioning
confidence: 99%